Strategi Pembelajaran Efektif Untuk Mengatasi Kesulitan Belajar Matematika Pada Siswa Sekolah Dasar - Sofiyah, Khotna; Khotimah Ritonga, Khusnul; Yuliana Lubis, Riska; Sari Rambe, Winda (PT. Alahyan Publisher Sukabumi, 2025)
There are still many elementary school age children who have learning difficulties in understanding and subtraction arithmetic operations presented in the form of story questions and difficulties in multiplication and division arithmetic operations. The purpose of this study was to determine the difficulties in learning mathematics for elementary school aged children and provide solutions or alternative solutions to overcome these learning difficulties. This research is a descriptive research using a qualitative approach. The subjects of this study were elementary school age students. Data collection techniques using document studies. The results showed that learning difficulties in mathematics were: 1) Difficulties in completing addition and subtraction in the form of math story problems; 2) Difficulty in completing mathematical multiplication and division arithmetic operations. The conclusing of this study is that there are difficulties in learning mathematics in elementary school students in the form of difficulties in addition and subtraction arithmetic operations which are presented in the form of story questions and difficulties in multiplication and division arithmetic operations. Therefore, an effective learning strategy is needed to overcome mathematics learning difficulties in elementary school students.